2006
DOI: 10.2134/agronj2005.0168
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Glyphosate‐Resistant Canola in Western Canadian Cropping Systems

Abstract: Canola (Brassica napus L.) is the most important oilseed crop in western Canada. Its prevalence across the Canadian Prairies influences the occurrence and impact of canola volunteers as weeds. Here we determined the persistence of canola seed in cropping systems so effective volunteer management strategies can be developed. In mid‐ to late‐October of 2000, approximately 770 seeds m−2 of glyphosate [N‐(phosphonomethyl)glycine]–resistant (GR) canola were scattered on plot areas at seven western Canadian sites. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
20
2
Order By: Relevance
“…In the 85 fields where volunteer canola was present, the mean density of 85.7 volunteer canola plants m (2 in the spring decreased to 13.7 plants m (2 by autumn. Similar observations were made by Harker et al (2006) in a 4-yr study across western Canada, which showed highly variable seedling densities among the locations (0 to 179 plants m (2 ), despite identical initial seed bank populations. Volunteer B. napus densities declined to B5 plants m (2 after the first year of the study.…”
Section: Population Dynamicssupporting
confidence: 79%
See 1 more Smart Citation
“…In the 85 fields where volunteer canola was present, the mean density of 85.7 volunteer canola plants m (2 in the spring decreased to 13.7 plants m (2 by autumn. Similar observations were made by Harker et al (2006) in a 4-yr study across western Canada, which showed highly variable seedling densities among the locations (0 to 179 plants m (2 ), despite identical initial seed bank populations. Volunteer B. napus densities declined to B5 plants m (2 after the first year of the study.…”
Section: Population Dynamicssupporting
confidence: 79%
“…Rotations including glyphosateresistant crops did not increase the risk from volunteer canola. Harker et al (2006) compared the density of canola volunteers in a wheat-field pea-barley rotation and a fallow-field pea-fallow rotation with five different seeding system combinations comprised of seeding date and soil disturbance level at seven sites across western Canada. Treatment effects were not consistent among sites and only one comparison was significant in 1 yr where greater volunteer canola densities tended to be associated with increasing soil disturbance in the continuous cropping rotation.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…However, it is notable that in 2011 and 2013, volunteer canola was the most prominent species even after 2 yr between canola crops (or 1 yr in 2011). Canola is known to exhibit secondary seed dormancy (Gulden et al 2003) and persist for several years in western Canadian cropping systems (Harker et al 2006).…”
Section: Temperature and Precipitation (2008 á 2013)mentioning
confidence: 99%
“…Brassica napus crop harvest losses of over 3000 seeds m (2 are common in western Canadian agriculture, and create a large seedbank (Gulden 2003). The greatest numbers of volunteers are seen in the first growing season following a B. napus crop (Harker et al 2006), which, in western Canada, is commonly a cereal crop. Harker et al (2006) estimated volunteer B. napus populations in wheat fields after broadleaf herbicide application range from 2.7 to 4.7 plants m (2 .…”
mentioning
confidence: 99%
“…The greatest numbers of volunteers are seen in the first growing season following a B. napus crop (Harker et al 2006), which, in western Canada, is commonly a cereal crop. Harker et al (2006) estimated volunteer B. napus populations in wheat fields after broadleaf herbicide application range from 2.7 to 4.7 plants m (2 . Secondary seed dormancy allows volunteer B. napus to persist for 4 to 5 yr following a B. napus crop, potentially causing yield losses from weed competition (Simard et al 2002;Gulden 2003).…”
mentioning
confidence: 99%